Bridging the science - policy interface: A new era for South African research and the role of knowledge brokering - Godfrey, Linda; Funke, Nikki; Mbizvo, Carmel (South African Journal of Science, 2010)
Government departments and agencies are faced with issues of increasing socio-ecological complexities around environmental sustainability and global change, which require them to make decisions that have the potential to impact greatly on society and economies. As a result, they are under increasing pressure to develop policies that consider a wide spectrum of scientific and indigenous knowledge. It is acknowledged that in South Africa, as elsewhere, a gap typically exists between the scientific or research community and the policymaking community, due to a number of underlying reasons at both ends. This gap often results in a unidirectional 'push of evidence' by researchers to policymakers, with a hope that policymakers will take up these findings and use them in policy identification, formulation or implementation. To support the uptake of evidence in policy, it is also important to stimulate an environment of 'evidence pull' by the policy community from the research community, as well as increasing the dialogue between these communities. A model of knowledge brokering is proposed in this paper as a means to bridge this gap between science and policy and, thereby, ensure the uptake of evidence in policy development and implementation. This model looks at the need for institutional mechanisms, such as knowledge-brokering offices, both within research organisations and government departments. It also highlights the importance of researchers involving policymakers from the onset of their research process, with a continuous dialogue between the two parties, both during and after the research, as a means of increasing the likelihood of research uptake.